The Effect of Intensive Training Program On The Development of Some Motor, Physical, Functional Abilities and Fighting Efficiency Of Special Iraqi Forces - Abo-Jerry, Rhiad Abdulhusaien; Atia, Ammar Abbas (Journal of Physical Education, 2021)
The researcher aimed at identifying the effect of a training program on the development of fighting efficiency. The researchers used the experimental method on (32) fighters from the Iraqi special forces. The researcher designed special training that develops some functional and physical abilities as well as the fighting efficiency of Iraqi forces fighters. The program is applied for two months with (22) training sessions in a month with 5 – 6 sessions per week. The data was collected and treated using proper statistical operations to come up with conclusions.